Kinetic properties and EMG activity of normal and over-speed pedaling in track sprint cyclists: A case study - Liao, H. T.; Lin, Y. C.; Pandy, M.; Tang, W. T. (ISBS - Conference Proceedings Archive (Konstanz), 2013)
Track sprint cycling requires unique skills. We investigate the pedaling kinetics and muscle coordination of a male track sprinter (170cm, 65kg, peak power 1513W) to see if they differ from that of a non-sprinter, and if the subject`s own technique vary from normal riding to an under-load maximal cadence sprint. Two trials were collected using 3D motion capture technology. EMG signals of 8 leg muscles were recorded. Joint torque and power of each trial were calculated using a subject specific musculoskeletal model, with realistic pedal forces as input to our dynamic simulation. Flexion torque appears at the knee during its extension, different from the non-sprinters. Joint torque and power appears similar for both trials, but 6 of the 8 muscles showed differences in EMG patterns. These findings could potentially benefit the evolvement of training methods.